"That's the Area of Affluent People Where We Have No Access": Spatial Inequality, Gated Communities, and the End of Public Space in Dhaka, Bangladesh. Issue 4 (4th July 2022) - Nahar Lata, Lutfun
ABSTRACT: The literature suggests that the rise of gated communities causes a number of problems, creates spatial fragmentation and social exclusion, and works as a barrier to promoting urban diversity. Gated communities have grown in popularity in recent decades in Dhaka, Bangladesh. In contrast to the popular view that gated communities provide an extreme example of residential segregation, this article argues that the rise of gated communities creates a differentiated citizenship by blocking poor people's access to public space, which is vital for their livelihoods. Weaving together observation and ethnographic research in the Sattola slum in Dhaka and its adjacent gated community, Niketon, this article argues that poor slum residents' access to public space for livelihoods is regulated—in the name of security and preventing criminal activities—by the local gated community members' association, which reproduces spatial inequality. The study contributes to the literature on gated communities and social segregation by revealing that private governance takes various forms and is not always separate from local government bodies; rather, local government actors and homeowners' associations may work together to exclude other groups from gated communities in the name of security.